2017
DOI: 10.1016/j.freeradbiomed.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-regulated proteolysis of human CYP2B6 via the ubiquitin-proteasome system

Abstract: We showed previously that rat cytochrome P450 CYP2B1 undergoes NO-dependent proteasomal degradation in response to inflammatory stimuli, and that the related human enzyme CYP2B6 is also down-regulated by NO in primary human hepatocytes. To investigate the mechanism of CYP2B6 down-regulation, we made several cell lines (HeLa and HuH7 cells) in which native CYP2B6 or CYP2B6 with a C-terminal V5 tag (CYP2B6V5) are expressed from a lentiviral vector with a cytomegalovirus promoter. Native CYP2B6 protein was rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 47 publications
1
38
0
1
Order By: Relevance
“…Like several rat P450 enzymes [9, 15, 26] and human CYP2B6 [21], CYP51A1 protein is targeted for degradation when exposed to nitric oxide generated under inflammatory conditions by NOS2 or released from NO donor compounds. Three pieces of evidence support this conclusion: 1) the magnitude of down-regulation of the protein in response to DPTA is greater than that of the mRNA; 2) down-regulation of the protein has similar magitude in the presence or absence of the protein synthesis inhibitor cycloheximide; 3) down-regulation of V5-tagged CYP51A1 expressed from a lentivirus controlled by a cytomegalovirus CMV promoter is almost identical to that of the native protein expressed in the same cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Like several rat P450 enzymes [9, 15, 26] and human CYP2B6 [21], CYP51A1 protein is targeted for degradation when exposed to nitric oxide generated under inflammatory conditions by NOS2 or released from NO donor compounds. Three pieces of evidence support this conclusion: 1) the magnitude of down-regulation of the protein in response to DPTA is greater than that of the mRNA; 2) down-regulation of the protein has similar magitude in the presence or absence of the protein synthesis inhibitor cycloheximide; 3) down-regulation of V5-tagged CYP51A1 expressed from a lentivirus controlled by a cytomegalovirus CMV promoter is almost identical to that of the native protein expressed in the same cells.…”
Section: Discussionmentioning
confidence: 99%
“…This leads us to conclude that CYP51A1 undergoes proteasome-dependent degradation in response to NO. In studying the effect of NO on V5-tagged CYP2B6 in Huh7 cells, we have also routinely observed this partial effect of bortezomib [21]. However, CYP51A1 degradation appears to be largely independent of ubiquitination, because increases in HMM complexes indicative of CYP51A1 ubiquitination were not observed in the presence of DPTA plus proteasome inhibition, and HA-Ub-tagged CYP51A1 was only detected at very low levels in cells transfected with HA-Ub.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When cells are exposed to long-term nutrient deprivation and energy loss, an excess amount of lipolysis results in the production of ketone bodies, which are the end product of free fatty acid oxidation reaction and can be used as an energy source in muscle and neurons. Since not all cells have the ability to use ketone bodies as an energy source, the cells that cannot utilize these small molecules activate proteolysis as a response to starvation (Luo et al 2017;Lee et al 2017). Proteolysis can be activated in two different ways, depending on the tissue type and stress duration.…”
Section: Introductionmentioning
confidence: 99%
“…CYP2B6 is a member of the cytochrome P450 superfamily of enzymes that is closely related to drug metabolism (41). A recent study demonstrated that CYP2B6 may affect the metabolism of NO under inflammatory stimulation (42). The present study indicated that PTGS2, NOS3 and CYP2B6 are potential targets for Radix Angelicae biseratae in the treatment of OA, with high degree values in the 'target-target' network.…”
Section: Discussionmentioning
confidence: 54%